2011
DOI: 10.1080/17441692.2010.510479
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method assessment of beliefs and practice around breast cancer in Ethiopia: Implications for public health programming and cancer control

Abstract: A large proportion of breast cancer patients in Ethiopia present for biomedical care too late, or not at all, resulting in high mortality. This study was conducted to better learn of beliefs and practices among patients accessing breast cancer services in a large referral centre in Ethiopia. Using a mixed-method design, we interviewed 69 breast cancer patients presenting for care at Tikur Anbessa Hospital in Addis Ababa, Ethiopia, about their beliefs, experiences and perspectives on breast cancer. Awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 20 publications
5
54
1
2
Order By: Relevance
“…Despite the availability of information on breast cancer risk factors, eleven studies included in the review reported a number of women who indicated that they "don't know" the cause of their cancer when asked [9,14,16,[37][38][39][40]43,50,52]. It was found that 6-57% of women said that they did not know the Other factors, such as the socio-demographic background of participants in the included studies may have contributed to the variations in attribution prevalence observed.…”
Section: Unknown Origins (Don't Know)mentioning
confidence: 89%
See 4 more Smart Citations
“…Despite the availability of information on breast cancer risk factors, eleven studies included in the review reported a number of women who indicated that they "don't know" the cause of their cancer when asked [9,14,16,[37][38][39][40]43,50,52]. It was found that 6-57% of women said that they did not know the Other factors, such as the socio-demographic background of participants in the included studies may have contributed to the variations in attribution prevalence observed.…”
Section: Unknown Origins (Don't Know)mentioning
confidence: 89%
“…Fifteen of the 24 included studies found that most women with breast cancer attributed their own cancer, at least in part, to family history or genetics [9,13,15,16,24,[34][35][36][37][38][39][40][41][42][43].Across the quantitative studies reviewed, the proportion of the sample in each study who reported that family history was a leading or sole cause of breast cancer varied. For example, in Costanzo et al's, [13] study, 70.5% (n=56) of the sample agreed that genetics or heredity was a leading cause.…”
Section: Biological Attributionsmentioning
confidence: 99%
See 3 more Smart Citations